Perlindungan Hukum bagi Korban Kekerasan Dalam Rumah Tangga yang Dilakukan oleh Anggota Militer - Camelia Marcella Susianto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Legal protection for victims of domestic violence (KDRT) committed by members of the military is an important issue in the Indonesian legal system. Even though the state has regulated protection for victims of domestic violence through various regulations, such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence, cases of violence involving members of the military have their own particularities. A review from a criminal law perspective shows that military members involved in domestic violence often avoid criminal sanctions equivalent to civilian perpetrators, due to differences in the legal systems that apply in the military and civilian environments. Military criminal law which regulates criminal acts committed by military members, such as the Military Criminal Code (KUHPM), provides different rules regarding prosecution mechanisms and imposing sanctions. Therefore, it is important to analyze in depth how criminal law can provide fair protection for victims of domestic violence committed by members of the military, taking into account equality before the law and the fulfillment of victims' rights. This research aims to examine the legal challenges and solutions that can be taken to provide maximum legal protection for victims of domestic violence committed by members of the military in Indonesia.